THE INFLUENCE OF POLITICAL DYNASTY ON THREATS OR OPPORTUNITIES FOR THE FUTURE OF INDONESIAN DEMOCRACY - Aulia Ningrum, Nadin; Nayla Aulia, Bilqhis; Rembulan F, Riska; Indriastuti, Maya (INDONESIAN JOURNAL OF SOCIAL POLITIC AND POLICY STUDIES, 2024)
This article discusses political phenomena related to dynasties in Indonesia, which have become an important concern in the context of the country's democratic progress. dynastic politics is a term that refers to the custom in which political power is inherited within a family or group, which often results in a smaller concentration of power and a greater decline in political participation. This study investigates the effects of dynastic politics on Pancasila democracy. On the one hand, political dynasties have the potential to provide continuity and stability in leadership, as well as allowing political networks and resources to be accessed. On the contrary, this practice can hinder the regeneration of leaders, reduce responsibility, and reduce public trust in political institutions which aims to provide a deeper understanding of how dynastic politics can be both a threat and an opportunity for the massesfuture of Indonesian democracy.this goal is achieved through the use of a descriptive approach and empirical data analysis.By considering the social, cultural and economic context, this article concludes that structural reforms and increasing public participation in the political process are needed to maximize the positive potential and reduce the negative potential of dynastic politics.